The Effect of Bisphosphonates on Fracture Healing Time and Changes in Bone Mass Density: A Meta-Analysis - Gao, Yongquan; Liu, Xiaochen; Gu, Yuan; Song, Deye; Ding, Muliang; Liao, Lele; Wang, Junjie; Ni, Jiangdong; He, Guangxu (Frontiers in Endocrinology, 2021)
Background Osteoporosis is a common complication of acute fracture, which can lead to fracture delayed union or other complications and resulting in poor fracture healing. Bisphosphate is a common anti-osteoporosis drug, but its application in fracture patients is still controversial because of its inhibitory effect on bone resorption. Method Studies were acquired from literature databases in accordance with established inclusion criteria. Standard mean difference (SMD) and 95% confidence intervals (Cls) were calculated to evaluate the effectiveness of the bisphosphonates treatment in fracture patients. Data analysis was conducted with the Review Manager 5.4.1 software. Results A total of 16 studies involving 5022 patients obtained from selected databases were examined. As expected, bisphosphate had no significant effect on fracture healing time, but it could significantly increase BMD and prevent osteoporosis. Meanwhile, bisphosphate can inhibit both bone resorption and bone formation markers, resulting in low bone turnover state. Conclusion This meta-analysis showed that bisphosphonate have no significant effect on fracture healing time but they do increase the changes in BMD and reduce bone synthesis and resorption markers. Early application of bisphosphonates after injury in the appropriate patient population should be considered.